Adipokines, Metabolic Syndrome and Rheumatic Diseases - Vanessa Abella; Morena Scotece; Javier Conde; Verónica López; Verónica Lazzaro; Jesús Pino; Juan J. Gómez-Reino; Oreste Gualillo (Journal of Immunology Research)
The metabolic syndrome (MetS) is a cluster of cardiometabolic disorders that result from the increasing prevalence of obesity. The major components of MetS include insulin resistance, central obesity, dyslipidemia, and hypertension. MetS identifies the central obesity with increased risk for cardiovascular diseases (CVDs) and type-2 diabetes mellitus (T2DM). Patients with rheumatic diseases, such as rheumatoid arthritis, osteoarthritis, systemic lupus erythematosus, and ankylosing spondylitis, have increased prevalence of CVDs. Moreover, CVD risk is increased when obesity is present in these patients. However, traditional cardiovascular risk factors do not completely explain the enhanced cardiovascular risk in this population. Thus, MetS and the altered secretion patterns of proinflammatory adipokines present in obesity could be the link between CVDs and rheumatic diseases. Furthermore, adipokines have been linked to the pathogenesis of MetS and its comorbidities through their effects on vascular function and inflammation. In the present paper, we review recent evidence of the role played by adipokines in the modulation of MetS in the general population, and in patients with rheumatic diseases.